PERUBAHAN KANDUNGAN MIKROFLORA AKIBAT PENAMBAHAN STARTER Pediococcus acidilactici F-11 DAN GARAM SELAMA FERMENTASI PEDA - . Rinto (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2010)
Peda is one of traditional fermented fish product. The addition of culture starter gives effect towards fermentation process. The purpose of this research was to know has present of microflora / microorganisms during fish fermentation by Pediococcus acidilactici F-11 as a starter. Peda was processed from Indiana mackerel fish (Rastrelliger neglectus) with different salt concentrations i.e. 20%, 25%, and 30%, with P. acidilactici F-11 was used as a starter. Batch without starter was used as a control. The result showed that peda with P. acidilactici as starter can decreased coliform number to 2 log cycles from 1,3 x 106 to 1,7 x 104 CFU and reduced histamine forming bacteria to 3 log cycle from 1,2 x 106 to 3,8 x 103 CFU in start of fish fermentation process, but in the end of process, the numbers of bacteria was not different, so P. acidilactici F-11 as starter was effective used in start of fish fermentation process.Keywords: Pediococcus acidilactici F-11, microorganism, peda.